Tinjauan Yuridis Praktek Pembagian Warisan Di Kalangan Muslim (Studi Kasus Di Dukuh Tegalsari Kec Teras, Kab Boyolali) - Ashari, Esa Riza, Mutimatun Ni'ami, S.H., M.Hum, Darsono, S.H., M.H (2016)
This study aimed to describe the division of inheritance in the village Tegalsari and describe Islam views devision inheritance practices implemented by the Hamlet Tegalsari. The research method using descriptive empirical jurisdiction. Sources of primary data, interviews and secondary data sources of primary law, secondary and tertiary. Data were collected by interview and literature study then analyzed the data qualitatively. The results showed that practices division of inheritance in the village Tegalsari use the legal system of inheritance customs, with the system for the flat where the division of inheritance boys and girls 1: 1 or equally, although nearly all the residents in the village of Tegalsari Muslims, it this is done to ensure and maintain harmony and unity of the family so that there are no disputes between families. Islam regards the division of inheritance practices such as al-u'rf saheeh which occurred in a particular community and the division can be considered legitimate for people who cultivate, because the elements of fairness and willingness to think of a society is the result of an agreement between the heirs and environmental conditions.